Detecção de anticorpos contra Leptospira spp. em jacarés-tinga caiman crocodilus (Linnaeus, 1758) de vida livre da região do médio rio Araguaia - Oliveira, Sérgio Rodrigo Pereira de (2014)
In Brazil, the extensive beef cattle is one of the pillars of the marshy and poorly explored regions economy. As a consequence, cattle and wild animals share the same environment, facilitating a possible cross transmission of infectious diseases between them and even to humans, once they may be infected by direct contact with urine, blood and tissues from carriers animals or by indirect contact, by water and/or contaminated solids by urine of infected animals. This research was conducted with the goal of detecting agglutinins anti-Leptospira spp. in blood serum samples of free-ranging spectacled caiman (Caiman crocodilus) from two distinct areas of middle region of Araguaia river, Mato Grosso and Goiás, and identify the most frequent serovars in these animals. Using the technique of the microscopic agglutination test (MAT), were tested 75 blood serum samples against 22 serovars of Leptospira interrogans. Of these samples, 59 (78.67%) were seropositive. The most frequent serovars found in C. crocodilus from the middle Araguaia river region were Patoc, Pyrogenes and Pyrogenes/Tarassovi with maximum titles of 1600, 1600 and 800, respectively. This work was the first to report the presence of anti-Leptospira spp. in C. crocodilus, suggesting that these animals may be natural or maintenance hosts of serovars Patoc and Pyrogenes.